ANALISIS COST VOLUME PROFIT DALAM UPAYA MERENCANAKAN LABA USAHA KOPI MACRO COFFEE ROASTERY - Ulfah Setia Iswara; Teguh Gunawan Setyabudi; Shinta Setiadevi (Universitas Nusa Cendana, 2023)
The purpose of this study was to determine the application of CVP analysis as a means of planning the expected profit in the future. The method used is a descriptive method with a case study approach. This study uses data in the form of financial information consisting of income and expenses, both fixed costs and variable costs. The results of the analysis carried out showed that the contribution margin for 2020 was IDR193,898,400 with a ratio of 69%. The break-even point for 2020 is IDR 37,147,900. The sales level of IDR281,473,400 was above the break-even point, so the sales made were said to be able to generate maximum profit. The safety limit for 2020 is 80%. The level of company security is quite high, it is said to be good because the possibility of loss is low. The minimum allowable sales amount (margin of safety) in 2020 is IDR 227,635,800. The amount of profit expected for 2020 is IDR 192,803,100, therefore the company must be able to achieve the sales target of IDR 333,262,300. CVP analysis can be useful for company management to assist in planning expected profits in the future. Keywords: Cost Volume Profit; Break Event Point; Contribution Margin; Margin of Safety